2013
DOI: 10.1177/0954407013506182
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cylinder deactivation on the emissions and fuel economy of a four-cylinder direct-injection diesel engine

Abstract: The potential benefits and limitations of deactivating two of four cylinders by cam switching to disable the intake and exhaust valve lift were investigated experimentally on a turbocharged four-cylinder common-rail direct-injection diesel engine. When running on two firing cylinders, at light engine loads (a brake mean effective pressure of 2 bar, based on four-cylinder operation), the brake specific fuel consumption at given engine-out nitrogen oxide levels is comparable with or marginally better than when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…This was shown in Ref. [18] to offer significant reductions in engine-out emissions of soot, CO and HC. Cylinder deactivation raised exhaust gas temperature, with the potential to raise the warm-up rate and operating temperature of after treatment components to the advantage of after treatment system performance at light loads.…”
Section: Introductionmentioning
confidence: 91%
“…This was shown in Ref. [18] to offer significant reductions in engine-out emissions of soot, CO and HC. Cylinder deactivation raised exhaust gas temperature, with the potential to raise the warm-up rate and operating temperature of after treatment components to the advantage of after treatment system performance at light loads.…”
Section: Introductionmentioning
confidence: 91%
“…Production diesel engines do not currently implement CDA. Previous work by several of the co-authors, and others, has shown that diesel engine CDA exhibits a beneficial thermal impact on the aftertreatment system (Leone and Pozar, 2001;Zammit et al, 2014;Ding et al, 2015;Garg et al, 2016;Joshi et al, 2017). Joshi et al demonstrated 3% fuel savings when CDA is implemented at idle during the heavy-duty federal test procedure (HDFTP) (Joshi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, in modern design of internal combustion engines, some advanced technologies, such as cylinder deactivation (CDA), variable valve actuation (VVA), turbo-charging system, and stop-start management [ 29 , 30 ], have been widely adopted to reduce the emissions and improve the fuel economy [ 31 ]. In these technologies, the CDA is usually adopted in multi-cylinder engines, and can output a desired power by varying the number of active cylinders [ 32 , 33 ]. Although the CDA shows potential for improving fuel economy, it also promotes certain undesired side-effects in some engine conjunctions because the working condition changes greatly (ex.…”
Section: Introductionmentioning
confidence: 99%